A method for preparing battery-grade lithium carbonate from clay-type lithium ore

Through multi-step processes, including roasting, leaching, iron removal, lithium-aluminum separation, decalcification and magnesium and deep purification, the problems of low extraction efficiency and low resource recovery of battery-grade lithium carbonate are successfully solved, and the preparation of high-purity lithium carbonate and efficient resource recovery are achieved.

CN119080035BActive Publication Date: 2025-04-18BEIJING MINING & METALLURGICAL TECH GRP CO LTD

Patent Information

Application Number
CN202411278182.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-04-18
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

The existing methods for preparing battery-grade lithium carbonate in clay-type lithium ore have problems such as low extraction efficiency, low resource recovery rate, complex process and high cost.

Method used

Battery-grade lithium carbonate is prepared by calcining, leaching, iron removal, reaction with inorganic alkali, separation of lithium aluminum, decalcification and magnesium treatment, deep purification and impurity removal, and reaction with sodium carbonate.

Benefits of technology

The efficient extraction of lithium and the full recovery of resources were achieved, and high-purity battery-grade lithium carbonate was prepared. The comprehensive recovery rate of lithium reached more than 82%, the comprehensive recovery rate of aluminum reached more than 55%, and high-grade alumina products were produced by-products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119080035B_ABST
    Figure CN119080035B_ABST
Patent Text Reader

Abstract

The present application provides a method for preparing battery-grade lithium carbonate from clay-type lithium ore, and relates to the field of resource utilization of clay-type lithium ore. The method for preparing battery-grade lithium carbonate from clay-type lithium ore includes: roasting, leaching, and deironing the clay-type lithium ore to obtain a deironed solution; mixing the deironed solution with an inorganic base to react to obtain a lithium-containing aluminum hydroxide precipitate adsorbent; performing lithium-aluminum separation on the lithium-containing aluminum hydroxide precipitate adsorbent to obtain aluminum oxide powder and a lithium-containing solution; performing calcium and magnesium removal treatment on the lithium-containing solution and concentrating it into a lithium-rich solution; deeply purifying and removing impurities from the lithium-rich solution to obtain a purified lithium-rich solution; reacting the purified lithium-rich solution with sodium carbonate to obtain battery-grade lithium carbonate. The present application can make full use of the lithium resources in the clay-type lithium ore, with a high resource utilization rate of lithium, and can produce high-value-added battery-grade lithium carbonate. The present application can also make full use of the aluminum resources in the clay-type lithium ore to produce high-grade alumina products as a by-product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of resource utilization of clay-type lithium ore, and in particular to a method for preparing battery-grade lithium carbonate from clay-type lithium ore. Background Art

[0002] Lithium is a silvery-white alkali metal element with a wide range of uses, including batteries, energy storage materials, ceramics, glass, lubricants, refrigerants, nuclear industry, and optoelectronics.

[0003] In recent years, with the rapid development of new energy vehicles and energy storage industries, the demand for lithium has increased dramatically. At present, lithium resources are usually classified into three categories: hard rock type (spodumene, lithium mica, and petalite), brine type (salt lake brine, oilfield brine) and clay type (aluminous mudstone, carbonaceous mudstone). The grade of hard rock lithium ore is declining year by year, the production cost is high, and the domestic lithium concentrate resources for lithium extraction from spodumene mainly rely on imported resources; while the lithium content in salt lake resources is low, the inorganic salt impurity composition is complex, and the magnesium content is very high. It is difficult to expand production capacity in the short term due to the local basic conditions and climate of the salt lake, as well as the more stringent environmental protection and ecological requirements for lithium extraction in the future. Therefore, the development and utilization of clay-type lithium ore resources have attracted attention and become an important resource for the production of lithium salt products in the future. It is particularly important and urgent to develop the process of extracting lithium from clay-type lithium ore. In my country, clay-type lithium ore resources are mainly distributed in Henan, Guangxi, Guizhou, Yunnan and Chongqing.

[0004] There are many defects in the existing methods of preparing battery-grade lithium carbonate from clay-type lithium ore. On the one hand, due to the complex occurrence state of lithium in clay-type lithium ore and the difficulty in processing, the extraction efficiency of existing extraction methods is low and lithium resources cannot be fully utilized; on the other hand, the extraction process is often accompanied by the leaching of other metal elements, but the resource recovery rate of existing technologies is not high, resulting in serious waste of resources. In addition, some extraction methods also have problems such as complex processes and high costs. Summary of the invention

[0005] The purpose of this application is to provide a method for preparing battery-grade lithium carbonate from clay-type lithium ore to solve the above-mentioned problems.

[0006] To achieve the above objectives, this application adopts the following technical solutions:

[0007] A method for preparing battery-grade lithium carbonate from clay-type lithium ore, comprising:

[0008] The clay-type lithium ore is roasted, leached and iron-removed to obtain an iron-removed solution;

[0009] The iron-removed solution is mixed with an inorganic base to react to obtain a lithium-containing aluminum hydroxide precipitate adsorbent;

[0010] Separating the lithium from the aluminum hydroxide precipitate adsorbed lithium to obtain aluminum oxide powder and a lithium-containing solution;

[0011] The lithium-containing solution is subjected to a decalcification and magnesium treatment and a concentration treatment to obtain a lithium-rich solution;

[0012] Deeply purifying and removing impurities from the lithium-rich solution to obtain a purified lithium-rich solution;

[0013] The purified lithium-rich solution is reacted with sodium carbonate to obtain battery-grade lithium carbonate.

[0014] According to an embodiment of the present application, the pH of the reaction system after the iron removal solution is mixed with the inorganic base is 5.0-7.0;

[0015] And / or, the temperature of the reaction between the deironing solution and the inorganic base is 40° C. to 70° C.;

[0016] And / or, the inorganic base comprises NaOH.

[0017] According to an embodiment of the present application, the lithium-aluminum separation of the lithium-containing aluminum hydroxide precipitate adsorbent includes: calcining the lithium-containing aluminum hydroxide precipitate adsorbent to obtain a calcined product; mixing the calcined product with water and an additive to leach lithium attached to the calcined product, filtering, and obtaining aluminum oxide and a lithium-containing solution;

[0018] Wherein, the additives include NaCl, NH 4 Cl, CaCl 2 MgCl 2 At least one of;

[0019] The content of the additive in the solution formed by the water and the additive is 1-6 wt %.

[0020] According to an embodiment of the present application, the calcination temperature is 350°C to 500°C;

[0021] And / or, the pH of the solution during the mixed leaching is 5 to 9;

[0022] And / or, the temperature of the mixed leaching is 40°C to 70°C.

[0023] According to an embodiment of the present application, the lithium-containing solution is subjected to a calcium-magnesium removal treatment and concentrated into a lithium-rich solution, comprising:

[0024] The lithium-containing solution is mixed with a decalcification and magnesium removal agent to carry out a decalcification and magnesium removal reaction to obtain a calcium and magnesium slag and a solution after decalcification and magnesium removal;

[0025] The solution after calcium and magnesium removal is evaporated and concentrated to obtain a lithium-rich solution.

[0026] According to an embodiment of the present application, the decalcification and magnesium reagent includes at least one of sodium carbonate and EDTA;

[0027] and / or, the concentration of the decalcification and magnesium reagent in the reaction system is 5-10wt%;

[0028] And / or, the pH of the decalcification and magnesium removal reaction is 9.0-10;

[0029] And / or, the temperature of the decalcification and magnesium removal reaction is 20°C to 25°C;

[0030] And / or, the concentrations of calcium and magnesium ions in the solution after calcium and magnesium removal are both less than 0.02 g / L;

[0031] and / or, the concentration of calcium ions in the lithium-rich solution is less than 50 mg / L, and the concentration of magnesium ions in the lithium-rich solution is less than 16 mg / L;

[0032] According to an embodiment of the present application, deep purification and impurity removal of the lithium-rich solution includes: mixing the lithium-rich solution with an ion exchange resin, removing impurity ions through the action of the ion exchange resin, and obtaining a purified lithium-rich solution through a separation step.

[0033] According to an embodiment of the present application, reacting the purified lithium-rich solution with sodium carbonate comprises: adding the lithium-rich solution to a saturated sodium carbonate solution to react;

[0034] And / or, the temperature at which the purified lithium-rich solution reacts with sodium carbonate is 85-95° C.;

[0035] And / or, the excess coefficient of sodium carbonate is 1.1 to 1.2;

[0036] And / or, the addition time of the lithium-rich solution is 30 to 40 minutes, the reaction time of the purified lithium-rich solution and sodium carbonate is 60 to 70 minutes, and the method further includes standing after the reaction is completed, and then filtering; the standing time is 30 to 40 minutes.

[0037] According to an embodiment of the present application, after the purified lithium-rich solution reacts with sodium carbonate, the method further comprises: filtering the ore pulp after the reaction to obtain lithium carbonate precipitate and lithium precipitation liquid; washing the lithium carbonate precipitate with water for multiple times to obtain battery-grade lithium carbonate;

[0038] And / or, the washing is performed for more than 2 times and the washing temperature is 85-95°C.

[0039] According to an embodiment of the present application, the roasting, leaching and iron removal of clay-type lithium ore includes:

[0040] Roasting the clay-type lithium ore to obtain roasted sand;

[0041] The roasted sand is mixed with an inorganic acid and leached to obtain a leachate;

[0042] The leaching solution is mixed with the roasted sand and calcium oxide, iron is removed, and then filtered to obtain iron slag and a solution after iron removal.

[0043] Compared with the prior art, the beneficial effects of this application include:

[0044] The present application provides a method for preparing battery-grade lithium carbonate from clay-type lithium ore. The present application can use clay-type lithium ore to prepare battery-grade lithium carbonate and produce aluminum oxide as a by-product. Specifically, the lithium carbonate prepared in the present application reaches electronic grade Li 2 CO 3 -D 2 Standard, Li 2 CO 3 The purity is greater than 99.50%, and the comprehensive recovery rate of lithium reaches more than 82%; the comprehensive recovery rate of aluminum in this application reaches more than 55%, and the grade of by-product alumina reaches more than 75%, which can be exported as an alumina product; at the same time, the final tailings after inorganic acid leaching are high-silicon slag containing alumina, which can be used as a building material or building material additive. In general, the method of this application can make full use of the lithium resources in clay-type lithium mines, and the resource utilization rate of lithium is high, and high value-added battery-grade lithium carbonate can be produced. Moreover, the method of this application can also make full use of the aluminum resources in clay-type lithium mines and produce high-grade alumina products as by-products. Moreover, the method of this application also has the advantages of simple process and low production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0046] Figure 1 This is a flow chart of preparing lithium-containing aluminum hydroxide precipitate adsorbent from clay-type lithium ore in Example 1;

[0047] Figure 2 This is a flow chart of lithium aluminum separation and by-production of aluminum oxide in Example 1;

[0048] Figure 3 Flow chart of preparing battery-grade lithium carbonate from the lithium-containing solution in Example 1. DETAILED DESCRIPTION

[0049] As used herein:

[0050] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0051] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0052] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0053] In these examples, parts and percentages are by mass unless otherwise indicated.

[0054] "Mass parts" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass parts of component A are a parts and the mass parts of component B are b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass parts of all components is not limited to 100 parts.

[0055] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0056] The present application provides a method for preparing battery-grade lithium carbonate from clay-type lithium ore, comprising:

[0057] The clay-type lithium ore is roasted, leached and iron-removed to obtain an iron-removed solution;

[0058] The iron-removed solution is mixed with an inorganic base to react to obtain a lithium-containing aluminum hydroxide precipitate adsorbent;

[0059] Separating the lithium from the aluminum hydroxide precipitate adsorbed lithium to obtain aluminum oxide powder and a lithium-containing solution;

[0060] The lithium-containing solution is subjected to a decalcification and magnesium treatment and a concentration treatment to obtain a lithium-rich solution;

[0061] Deeply purifying and removing impurities from the lithium-rich solution to obtain a purified lithium-rich solution;

[0062] The purified lithium-rich solution is reacted with sodium carbonate to obtain battery-grade lithium carbonate.

[0063] In the iron-removed solution obtained after roasting, leaching and iron removal treatment, the aluminum content in the solution is much higher than the lithium content. The mass ratio of Al to Li in the lithium-aluminum solution is greater than 15, so lithium-aluminum separation is the key to extracting lithium and preparing battery-grade lithium carbonate.

[0064] According to the embodiment of the present application, the pH of the reaction system after the iron removal solution is mixed with the inorganic base is 5.0-7.0; at this pH, it is conducive to the preparation of amorphous aluminum hydroxide, and its ability to adsorb lithium reaches 100%. Through this operation, lithium aluminum in the solution can be separated from other impurity elements such as calcium, magnesium, manganese and trace amounts of heavy metals, and the aluminum hydroxide precipitate that adsorbs lithium can be washed to obtain a relatively pure product.

[0065] Illustratively, the pH of the reaction system after the iron-removed solution is mixed with the inorganic base can be 5.0, 5.2, 5.4, 5.5, 6.0, 6.2, 6.4, 6.5, 6.7, 6.9, 7.0 or any value between 5.0 and 7.0.

[0066] And / or, the temperature at which the iron-removed solution reacts with the inorganic base is 40° C. to 70° C.; at this temperature, amorphous aluminum hydroxide is favorable for preparing, and its lithium adsorption capacity reaches 100%.

[0067] Illustratively, the temperature at which the iron-removed solution reacts with the inorganic base may be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C or any value between 40°C and 70°C.

[0068] And / or, the inorganic base comprises NaOH.

[0069] According to an embodiment of the present application, the lithium-aluminum separation of the lithium-containing aluminum hydroxide precipitate adsorbent includes: calcining the lithium-containing aluminum hydroxide precipitate adsorbent to obtain a calcined product; mixing the calcined product with water and an additive to leach the lithium attached to the calcined product, filtering to obtain aluminum oxide and a lithium-containing solution. The lithium-containing solution is sent to the next step, and the aluminum oxide remains in the slag, which is the by-product aluminum oxide powder.

[0070] Wherein, the additives include NaCl, NH 4 Cl, CaCl 2 MgCl 2 At least one of;

[0071] The content of the additive in the solution formed by the water and the additive is 1-6 wt %.

[0072] Illustratively, the content of the additive in the solution formed by the water and the additive may be 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt% or any value between 1 and 6 wt%.

[0073] According to an embodiment of the present application, the calcination temperature is 350° C. to 500° C. At this temperature, aluminum hydroxide can be dehydrated and dehydroxylated to generate aluminum oxide.

[0074] Illustratively, the calcination temperature may be 350°C, 400°C, 450°C, 500°C, or any value between 350°C and 500°C.

[0075] And / or, the pH of the solution during the mixed leaching is 5 to 9;

[0076] Illustratively, the pH of the solution during the mixed leaching may be 5, 6, 7, 8, 9 or any value between 5 and 9.

[0077] And / or, the temperature of the mixed leaching is 40°C to 70°C.

[0078] Illustratively, the temperature of the mixed leaching may be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C or any value between 40°C and 70°C.

[0079] Lithium can be leached from the mixed solution of the calcined product, water and additives, and the recovery rate of lithium leaching is high, reaching more than 97.5%. Through this step, complete separation of lithium and aluminum can be achieved. The calcined product contains more than 75% alumina, which can be exported as a by-product.

[0080] The lithium-containing solution after lithium-aluminum separation has a lithium concentration of 2~3g / L, and contains calcium at a concentration of about 3g / L, magnesium at 0.5~1.0g / L, and trace amounts of other heavy metal elements; the use of chemical methods to initially remove calcium and magnesium can prevent scaling during evaporation and concentration.

[0081] According to an embodiment of the present application, the lithium-containing solution is subjected to a calcium-magnesium removal treatment and concentrated into a lithium-rich solution, comprising:

[0082] The lithium-containing solution is mixed with a decalcification and magnesium reagent to carry out a decalcification and magnesium reaction to obtain a calcium and magnesium slag and a solution after decalcification and magnesium removal;

[0083] The solution after calcium and magnesium removal is evaporated and concentrated to obtain a lithium-rich solution.

[0084] According to an embodiment of the present application, the decalcification and magnesium reagent includes at least one of sodium carbonate and EDTA;

[0085] And / or, the concentration of the decalcification magnesium reagent in the reaction system is 5-10wt%; the concentration of the decalcification magnesium reagent in the reaction system is low, and the concentration of lithium in the solution is low at this time. The reaction is carried out at room temperature (20-25°C), and the lithium in the solution is basically not precipitated. At this time, the decalcification magnesium reagent reacts with calcium and magnesium in the solution to generate insoluble precipitates of calcium and magnesium slag, such as calcium carbonate and magnesium carbonate. The obtained calcium and magnesium slag (such as calcium carbonate and magnesium carbonate) can be returned to the process and used as an agent for iron removal.

[0086] And / or, the pH of the decalcification and magnesium removal reaction is 9.0-10;

[0087] Exemplarily, the pH of the decalcification and magnesium removal reaction may be 9.0, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9, 10 or any value between 9.0 and 10.

[0088] And / or, the temperature of the decalcification and magnesium removal reaction is 20°C to 25°C;

[0089] Exemplarily, the temperature of the decalcification and magnesium removal reaction can be 20°C, 21°C, 22°C, 23°C, 24°C, 25°C or any value between 20°C and 25°C.

[0090] And / or, the concentrations of calcium and magnesium ions in the solution after calcium and magnesium removal are both less than 0.02 g / L;

[0091] The obtained calcium-magnesium slag can be returned as a neutralizing agent for reuse.

[0092] and / or, the concentration of calcium ions in the lithium-rich solution is less than 50 mg / L, and the concentration of magnesium ions in the lithium-rich solution is less than 16 mg / L;

[0093] According to an embodiment of the present application, deep purification and impurity removal of the lithium-rich solution includes: mixing the lithium-rich solution with an ion exchange resin, removing impurity ions through the action of the ion exchange resin, and obtaining a purified lithium-rich solution through a separation step; through this step, the Ca, Mg, Al, Fe, Cr and other ions in the solution can be almost 100% removed, the impurity elements remaining in the solution are less than 0.5 mg / L, and the solution meets the requirements for producing electronic-grade lithium carbonate.

[0094] And / or, the ion exchange resin includes domestic 001×7(732 # ) Any one of ordinary resin, HP-Ca resin, and CH-93 resin.

[0095] The concentrations of calcium and magnesium ions in the purified lithium-rich solution are both less than 0.5 mg / L, and the concentrations of heavy metal ions such as aluminum, iron, and manganese in the purified lithium-rich solution are both less than 0.1 mg / L. The solution meets the requirements for preparing battery-grade lithium carbonate.

[0096] According to an embodiment of the present application, reacting the purified lithium-rich solution with sodium carbonate comprises: adding the lithium-rich solution to a saturated sodium carbonate solution (inverse addition method) to react;

[0097] And / or, the temperature at which the purified lithium-rich solution reacts with sodium carbonate is 85-95° C.;

[0098] Exemplarily, the temperature at which the purified lithium-rich solution reacts with sodium carbonate may be 85°C, 90°C, 95°C, or any value between 85 and 95°C.

[0099] And / or, the excess coefficient of sodium carbonate is 1.1 to 1.2;

[0100] In the experiment, for a lithium-rich solution with a lithium concentration of 10.28 g / L, the lithium consumption was 86.36 kg / m 3 Sodium carbonate solution.

[0101] And / or, the addition time of the lithium-rich solution is 30~40min (for example, 30min, 35min, 40min or any value between 30~40min), the time for the purified lithium-rich solution to react with sodium carbonate is 60~70min (for example, 60min, 65min, 70min or any value between 60~70min), and the method further includes standing after the reaction is completed, and then filtering; the standing time is 30~40min (for example, 30min, 35min, 40min or any value between 30~40min).

[0102] According to an embodiment of the present application, after the purified lithium-rich solution reacts with sodium carbonate, the method further comprises: filtering the ore pulp after the reaction to obtain lithium carbonate precipitate and lithium precipitation liquid; washing the lithium carbonate precipitate with water for multiple times to obtain battery-grade lithium carbonate;

[0103] And / or, the washing is performed twice or more, and the washing temperature is 85-95° C. (eg, 85° C., 90° C., 95° C., or any value between 85-95° C.).

[0104] By washing the lithium carbonate precipitate, the entrained sodium carbonate can be removed so that the sodium ions in the product meet the standards.

[0105] According to the system water balance, the lithium concentration of the washed liquid is 1~2g / L and is returned to the process for reuse. The recovery rate of lithium carbonate precipitation can reach 70~80%. After two washes, the recovery rate of lithium carbonate product is 60%, reaching electronic grade Li 2 CO 3 -D 2 Standard, well-crystallized, uniform in size, clear rod-shaped particles, and good dispersibility.

[0106] According to an embodiment of the present application, the roasting, leaching and iron removal of clay-type lithium ore includes:

[0107] Roasting the clay-type lithium ore to obtain roasted sand;

[0108] The roasted sand is mixed with an inorganic acid and leached to obtain a leachate;

[0109] The leaching solution is mixed with the roasted sand and calcium oxide, iron is removed, and the mixture is filtered to obtain iron slag and a solution after iron removal.

[0110] By roasting the clay-type lithium ore, the lithium-containing mineral can be activated and transformed. Specifically, the clay-type lithium ore can be dry-ground to obtain the raw ore powder, and then roasted by gas-solid two-phase circulating fluidization. The roasting process is in a gas-solid suspension state, the roasting temperature is uniform, the gas-solid two-phase contact is sufficient, and the physical phase reconstruction of the raw ore during the roasting process is beneficial to the activation and transformation of the lithium-containing mineral, and the production of activated roasted sand is beneficial to the leaching of lithium and aluminum therein by inorganic acid.

[0111] The calcination temperature is 500° C. to 850° C.; calcination can produce porous calcined sand, which is convenient for efficient leaching of lithium using inorganic acid.

[0112] The inorganic acid includes sulfuric acid or hydrochloric acid;

[0113] The concentration of hydrochloric acid in the slurry solution obtained after the roasted sand is mixed with the inorganic acid is 50-200 g / L;

[0114] The leaching temperature is 50°C to 80°C;

[0115] After the leaching is completed, leaching residue and high-acid solution are obtained, and the concentration of hydrochloric acid in the high-acid solution is 5-50g / L; the leaching residue is sent for thickening and washing, and the washed leaching residue is a building material, and its silicon dioxide and aluminum oxide components together account for more than 80%, which is a high-silicon slag containing aluminum oxide and can be used as a building material.

[0116] After the leaching is completed, the method further includes: mixing the high-acid solution with the roasted sand, and performing a neutralization reaction at a temperature of 50-70° C. to obtain a leachate; in this step, the calcite or dolomite in the roasted sand can neutralize the residual acid in the high-acid solution, so that the pH of the leachate is 1.0-1.5.

[0117] The calcined sand is mixed with an inorganic acid for leaching, so that lithium, aluminum and iron in the calcined sand can be leached out, and the leaching solution contains lithium ions, aluminum ions and iron ions.

[0118] When performing the iron removal, air is introduced into the reaction system to control the pH value of the reaction system to be 1.8-2.2; the temperature for performing the iron removal is 50° C.-90° C.;

[0119] The time for carrying out the iron removal is 2 to 8 hours;

[0120] The content of the roasted sand is 5-15 kg / m 3 leachate;

[0121] Under the above conditions, the slurry has good filtering performance, high iron removal efficiency and lithium loss of less than 1.5%. After iron removal, the solution contains iron <0.1g / L, which meets the needs of lithium-aluminum separation. After iron removal, the solution is sent to the next process for lithium-aluminum separation. The obtained filter residue is iron slag, which is stored.

[0122] After roasted sand leaching and solution iron removal, the comprehensive leaching recovery of lithium can reach more than 90%.

[0123] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0124] Example 1

[0125] Example 1 provides a method for preparing battery-grade lithium carbonate from clay-type lithium ore, and the specific steps are as follows.

[0126] The main chemical components of the clay-type lithium ore in Example 1 are listed in Table 1.

[0127] Table 1 Chemical element composition of clay-type lithium ore in Example 1 (%)

[0128]

[0129] (1) Fluidized roasting of raw ore: reference Figure 1 , grinding the clay-type lithium ore to a particle size of less than 0.074 mm, accounting for 80%, and roasting the raw ore at 550°C to obtain activated raw ore roasted sand;

[0130] (2) Leaching of roasted ore and iron removal from leaching solution: The clay-type lithium ore roasted sand is subjected to high-acid leaching: the leaching temperature is 60°C, the leaching time is 4h, the leaching liquid-to-solid ratio is 2:1, and the hydrochloric acid concentration before leaching is 120g / L. After the leaching is completed, it is filtered and washed. The filtrate (high-acid feed solution) contains 30g / L of hydrochloric acid. The filter residue after washing is off-white, and the washing water is used for recycling the leaching solution; the high-acid feed solution is pre-neutralized with roasted sand under the conditions of leaching temperature of 70°C, leaching time of 4h, and leaching liquid-to-solid ratio of 2:1. The pH value of the ore pulp is maintained at 1.2. After the leaching is completed, it is directly filtered (without washing). The filtrate (primary feed solution) is sent to the next step for iron removal, and the filter residue is returned for high-acid leaching;

[0131] Iron removal from leaching liquid: The iron removal agent is calcium oxide + raw ore roasted sand, the reaction temperature is 70℃, and air is blown in at the same time. The air dosage in the stirring tank is 1.0m 3 / m 2 ·min, pressure rise 88kPa, end point pH value 2.2, reaction time 4h, the amount of raw ore roasted sand is 15kg / m 3 Liquid, CaO dosage 25 kg / m 3 After the reaction is completed, the slurry is filtered, and the filtrate (lithium-containing solution after iron removal) is sent to the next step for lithium-aluminum separation, and the filter residue is iron-containing slag.

[0132] Experimental studies have shown that the lithium leaching rate is 92.00%, the residual iron in the lithium-containing solution after iron removal is 0.05g / L, the lithium loss is 1.5%, and the aluminum leaching rate is 57.5%, with all of it remaining in the solution without loss.

[0133] (3) Preparation of aluminum hydroxide precipitate for lithium adsorption: The mass ratio of Al to Li in the lithium-aluminum solution is significantly greater than 15. NaOH is used as a neutralizer, the reaction pH is controlled at 5.5, and the reaction temperature is 70°C. Under these conditions, amorphous aluminum hydroxide is prepared, and its lithium adsorption capacity reaches 100%;

[0134] (4) Lithium-aluminum separation: reference Figure 2The aluminum hydroxide precipitate that absorbs lithium is subjected to low-temperature activation calcination at 400°C to dehydrate and dehydroxylate it. The calcined product is then placed in an aqueous solution with a pH value of 7, and NaCl is added to make its concentration in water 2% (the water preparation reagent is analytical grade). The lithium in the calcined product is leached at a temperature of 50°C to separate lithium and aluminum. At this time, the lithium enters the solution and is sent to the next step, while aluminum oxide remains in the slag, which is the by-product aluminum oxide powder. The lithium leaching recovery rate is high, reaching 97.5%, and lithium and aluminum are completely separated. The calcined product contains 75% aluminum oxide and can be exported as an aluminum oxide product.

[0135] (5) Deep purification and impurity removal of decalcified magnesium from lithium-containing solution and its concentrate: Reference Figure 3 The lithium-containing solution after lithium and aluminum separation has a lithium concentration of 2.5g / L, and contains 3g / L calcium, 0.8g / L magnesium, and trace amounts of heavy metal elements. First, a chemical method is used to preliminarily remove calcium and magnesium in order to prevent scaling during evaporation and concentration. The chemical reagent for decalcification and magnesium is sodium carbonate. Under the conditions of pH 10 and 25°C, the solution after decalcification and magnesium removal contains 0.01g / L calcium ions and 0.008g / L magnesium ions. The generated calcium and magnesium slag (calcium carbonate slag, magnesium carbonate slag) is returned for reuse as a neutralizing agent;

[0136] Subsequently, the lithium-containing solution is evaporated and concentrated. When the lithium ion concentration reaches 20 g / L, the calcium ion concentration in the concentrated lithium solution is 15 mg / L and the magnesium ion concentration is 3 mg / L.

[0137] The third step is to deeply purify and remove impurities from the concentrated lithium-containing solution: ion exchange resin is used to deeply adsorb metal ions such as calcium, magnesium, aluminum, and iron in the solution. # ) Ordinary resin, after deep impurity removal, the solution contains 0.5 mg / L calcium, 0.2 mg / L magnesium ions, and less than 0.1 mg / L heavy metal ions such as aluminum, iron, and manganese. The solution meets the requirements for preparing battery-grade lithium carbonate.

[0138] (6) Preparation of battery-grade lithium carbonate: Heat the deeply impurity-free lithium-rich solution and 40% sodium carbonate saturated solution to 90°C respectively, with a sodium carbonate dosage of 150 kg / m 3 , add the heated lithium-rich solution to the heated saturated sodium carbonate solution, react for 30 minutes, stir and react for 60 minutes, let stand for 30 minutes, filter the reaction slurry; the lithium carbonate precipitate filter cake is slurried and washed with pure water at a washing temperature of 90°C and washed twice;

[0139] The results of lithium precipitation tests show that the prepared lithium carbonate reaches electronic grade Li 2 CO 3 -D 2 Standard, Li 2CO 3 The purity is greater than 99.50%, and it is well crystallized, uniform in size, and appears as clear rod-shaped particles with good dispersibility.

[0140] In Example 1, the comprehensive recovery rate of lithium reached 82.5%, and the comprehensive recovery rate of aluminum reached 55.0%.

[0141] Example 2

[0142] Example 2 provides a method for preparing battery-grade lithium carbonate from clay-type lithium ore, and the specific steps are as follows.

[0143] The main chemical components of the clay-type lithium ore in Example 2 are listed in Table 2.

[0144] Table 2 Chemical element composition of clay-type lithium ore in Example 2 (%)

[0145]

[0146] (1) Roasting of raw ore: grinding clay-type lithium ore to a particle size of less than 0.074 mm, accounting for 87%, and roasting the raw ore at 580°C to obtain activated roasted sand;

[0147] (2) Roasted sand leaching and iron removal by leaching solution: The clay-type lithium ore roasted sand is subjected to high-acid leaching: the leaching temperature is 70°C, the leaching time is 4h, the leaching liquid-to-solid ratio is 2:1, and the hydrochloric acid concentration before leaching is 150g / L. After the leaching is completed, it is filtered and washed. The filtrate (high-acid feed solution) contains 40g / L of hydrochloric acid. The filter residue after washing is off-white, and the washing water is used for recycling the leaching solution; roasted sand is used to pre-neutralize the high-acid feed solution under the conditions of leaching temperature of 70°C, leaching time of 4h, and leaching liquid-to-solid ratio of 3:1. The pH value of the ore pulp is maintained at 1.5. After the leaching is completed, it is directly filtered (without washing). The filtrate (primary feed solution) is sent to the next step for iron removal, and the filter residue is returned for high-acid leaching;

[0148] Iron removal from leaching liquid: The iron removal agent is calcium oxide + raw ore roasted sand, the reaction temperature is 80℃, and air is blown in at the same time. The air consumption in the stirring tank is 1.5m 3 / m 2 ·min, pressure rise 88kPa, end point pH value 2.0, reaction time 4h, the amount of raw ore roasted sand is 15kg / m 3 Liquid, CaO dosage 25 kg / m 3 After the reaction is completed, the slurry is filtered, and the filtrate (lithium-containing solution after iron removal) is sent to the next step for lithium-aluminum separation, and the filter residue is iron-containing slag.

[0149] Experimental studies have shown that the lithium leaching rate is 93.50%, the residual iron in the lithium-containing solution after iron removal is 0.02g / L, the lithium loss is 2.5%, and the aluminum leaching rate is 59%.

[0150] (3) Preparation of aluminum hydroxide precipitate for lithium adsorption: The mass ratio of Al to Li in the lithium-aluminum solution is significantly greater than 15. NaOH is used as a neutralizer, the reaction pH is controlled at 6.2, and the reaction temperature is 50°C. Under these conditions, amorphous aluminum hydroxide is prepared, and its lithium adsorption capacity reaches 100%;

[0151] (4) Lithium-aluminum separation: The aluminum hydroxide precipitate that adsorbs lithium is subjected to low-temperature activation calcination at 350°C to dehydrate and dehydroxylate it. NaCl is added to the calcined product in an aqueous solution with a pH value of 8 to make its concentration in water 4% (the water preparation reagent is of analytical grade). The lithium in the calcined product is leached at a temperature of 70°C to separate the lithium and aluminum. At this time, the lithium enters the solution and is sent to the next step, while the aluminum oxide remains in the slag, which is the by-product aluminum oxide powder. The lithium leaching recovery rate is high, reaching 98.5%, and the lithium and aluminum are completely separated. The obtained calcined product contains an aluminum oxide grade of 78%, which can be exported as an aluminum oxide product;

[0152] (5) Decalcification and magnesium of lithium-containing solution and deep purification and impurity removal of its concentrated solution: The lithium-containing solution after lithium and aluminum separation has a lithium concentration of 3.0 g / L, and contains 3 g / L calcium, 0.8 g / L magnesium, and trace amounts of heavy metal elements. First, a chemical method is used to preliminarily remove calcium and magnesium in order to prevent scaling during evaporation and concentration. The chemical reagent for decalcification and magnesium is sodium carbonate. Under the conditions of pH 10 and 25°C, the solution after decalcification and magnesium removal contains 0.006 g / L calcium ions and 0.003 g / L magnesium ions. The generated calcium and magnesium slag (calcium carbonate slag, magnesium carbonate slag) is returned for reuse as a neutralizing agent;

[0153] Subsequently, the lithium-containing solution is evaporated and concentrated. When the lithium ion concentration reaches 25 g / L, the calcium ion concentration in the concentrated lithium solution is 20 mg / L and the magnesium ion concentration is 5 mg / L.

[0154] The third step is to deeply purify and remove impurities from the concentrated lithium-containing solution: the ion exchange resin method is used to deeply adsorb metal ions such as calcium, magnesium, aluminum, and iron in the solution. A special special-effect resin material, CH-93 resin, is used. After deep impurity removal, the solution contains 0.2 mg / L calcium, 0.08 mg / L magnesium ions, and less than 0.1 mg / L heavy metal ions such as aluminum, iron, and manganese. The solution meets the requirements for preparing battery-grade lithium carbonate.

[0155] (6) Preparation of battery-grade lithium carbonate: The operating conditions of this step in Example 2 are the same as those in Example 1. The results of the lithium precipitation test after lithium-rich purification show that the prepared lithium carbonate reaches electronic grade Li 2 CO 3 -D 2 Standard, Li 2 CO 3The purity is greater than 99.50%, and it is well crystallized, uniform in size, and appears as clear rod-shaped particles with good dispersibility.

[0156] In Example 2, the comprehensive recovery rate of lithium reached 84.5%, and the comprehensive recovery rate of aluminum reached 57.0%.

[0157] Example 3

[0158] Example 3 provides a method for preparing battery-grade lithium carbonate from clay-type lithium ore, and the specific steps are as follows.

[0159] The main chemical components of the clay-type lithium ore in Example 3 are listed in Table 3.

[0160] Table 3 Chemical element composition of clay-type lithium ore in Example 3 (%)

[0161]

[0162] (1) Roasting of raw ore: grinding clay-type lithium ore to a particle size of less than 0.074 mm, accounting for 90%, and roasting the raw ore at 620°C to obtain activated roasted sand;

[0163] (2) Roasted sand leaching and iron removal by leaching solution: The clay-type lithium ore roasted sand is subjected to high-acid leaching: the leaching temperature is 70°C, the leaching time is 4h, the leaching liquid-to-solid ratio is 3:1, and the hydrochloric acid concentration before leaching is 120g / L. After the leaching is completed, it is filtered and washed. The filtrate (high-acid feed solution) contains 25g / L of hydrochloric acid. The filter residue after washing is off-white, and the washing water is used for recycling the leaching solution; roasted sand is used to pre-neutralize the high-acid feed solution under the conditions of leaching temperature of 70°C, leaching time of 4h, and leaching liquid-to-solid ratio of 2:1. The pH value of the ore pulp is maintained at 1.5. After the leaching is completed, it is directly filtered (without washing). The filtrate (primary feed solution) is sent to the next step for iron removal, and the filter residue is returned for high-acid leaching;

[0164] Iron removal from leaching liquid: The iron removal agent is calcium oxide + raw ore roasted sand, the reaction temperature is 70℃, and air is blown in at the same time. The air consumption in the stirring tank is 1.5m 3 / m 2 ·min, pressure rise 88kPa, end point pH value 2.0, reaction time 4h, the amount of raw ore roasted sand is 15kg / m 3 Liquid, CaO dosage 25 kg / m 3 After the reaction is completed, the slurry is filtered, and the filtrate (lithium-containing solution after iron removal) is sent to the next step for lithium-aluminum separation, and the filter residue is iron-containing slag.

[0165] Experimental studies have shown that the lithium leaching rate is 92.50%, the residual iron in the lithium-containing solution after iron removal is 0.01g / L, the lithium loss is 1.5%, and the aluminum leaching rate is 62%.

[0166] (3) Preparation of aluminum hydroxide precipitate for lithium adsorption: The mass ratio of Al to Li in the lithium-aluminum solution is significantly greater than 15. NaOH is used as a neutralizer, the reaction pH is controlled at 6.5, and the reaction temperature is 55°C. Under these conditions, amorphous aluminum hydroxide is prepared, and its lithium adsorption capacity reaches 100%;

[0167] (4) Lithium-aluminum separation: The aluminum hydroxide precipitate adsorbing lithium is subjected to low-temperature activation calcination at 380°C to dehydrate and dehydroxylate it. The calcined product is placed in an aqueous solution with a pH of 9 and CaCl is added. 2 The concentration of the calcined product is 2% in water (the water is analytical grade), and the lithium in the calcined product is leached at a temperature of 55°C to separate the lithium and aluminum. At this time, the lithium enters the solution and is sent to the next step, while the aluminum oxide remains in the slag, which is the by-product aluminum oxide powder. The lithium leaching recovery rate is high, reaching 97.5%, and the lithium and aluminum are completely separated. The calcined product contains an aluminum oxide grade of 80%, which can be exported as an aluminum oxide product;

[0168] (5) Decalcification and magnesium of lithium-containing solution and deep purification and impurity removal of its concentrated solution: The lithium-containing solution after lithium and aluminum separation has a lithium concentration of 2.0g / L, and contains 0.5g / L calcium, 0.6g / L magnesium, and trace amounts of heavy metal elements. First, a chemical method is used to preliminarily remove calcium and magnesium in order to prevent scaling during evaporation and concentration. The chemical reagent for decalcification and magnesium is sodium carbonate. Under the conditions of pH 10 and 25°C, the solution after decalcification and magnesium removal contains 0.01g / L calcium ions and 0.015g / L magnesium ions. The generated calcium and magnesium slag (calcium carbonate slag, magnesium carbonate slag) is returned for reuse as a neutralizing agent;

[0169] Subsequently, the lithium-containing solution is evaporated and concentrated. When the lithium ion concentration reaches 18 g / L, the calcium ion concentration in the concentrated lithium solution is 10 mg / L and the magnesium ion concentration is 15 mg / L.

[0170] The third step is to deeply purify and remove impurities from the concentrated lithium-containing solution: the ion exchange resin method is used to deeply adsorb metal ions such as calcium, magnesium, aluminum, and iron in the solution. A special special-effect resin material, CH-93 resin, is used. After deep impurity removal, the solution contains 0.2 mg / L calcium, 0.08 mg / L magnesium ions, and heavy metal ions such as aluminum, iron, and manganese are all less than 0.1 mg / L. The solution meets the requirements for preparing battery-grade lithium carbonate.

[0171] (6) Preparation of battery-grade lithium carbonate: The operating conditions of this step in Example 3 are the same as those in Example 1. The results of the lithium precipitation test after lithium-rich purification show that the prepared lithium carbonate reaches electronic grade Li 2 CO 3 -D 2 Standard, Li 2 CO 3The purity is greater than 99.50%, and it is well crystallized, uniform in size, and appears as clear rod-shaped particles with good dispersibility.

[0172] In Example 3, the comprehensive recovery rate of lithium reached 82.5%, and the comprehensive recovery rate of aluminum reached 60.0%.

[0173] Comparative Example 1

[0174] The method of reference example 1 uses clay-type lithium ore to prepare battery-grade lithium carbonate. The other steps are the same as those of example 1, except that when lithium-aluminum separation is performed on the lithium-containing aluminum hydroxide precipitate adsorbent, the additive NaCl in step (4) is omitted in reference example 1.

[0175] In Comparative Example 1, no additives were used for strengthening, and the lithium leaching recovery rate in step (4) was only 92.5%, while in Example 1, NaCl was used for co-leaching, and the lithium leaching recovery rate in step (4) was 97.5%.

[0176] Comparative Example 2

[0177] Referring to the method of Example 1, battery-grade lithium carbonate is prepared using clay-type lithium ore. The other steps are the same as those of Example 1, except that: in step (5), the lithium-containing solution is not subjected to calcium and magnesium removal treatment in Comparative Example 2, and the lithium-containing solution is directly evaporated and concentrated in Comparative Example 2.

[0178] In Comparative Example 2, the lithium-containing solution is not pre-decalcified and magnesium-free, and a large amount of scaling is generated when the lithium-containing solution is evaporated and concentrated, and electronic-grade lithium carbonate cannot be produced. Therefore, the pre-decalcification and magnesium-free step of the lithium-containing solution cannot be omitted.

[0179] Comparative Example 3

[0180] The method of Reference Example 3 uses clay-type lithium ore to prepare battery-grade lithium carbonate. The other steps are the same as those of Example 3, except that: Reference Example 3 does not perform deep purification and impurity removal, that is, the third step in step (5) is omitted. Reference Example 3 directly reacts the lithium-rich solution after evaporation and concentration in step (5) with sodium carbonate to prepare battery-grade lithium carbonate.

[0181] The lithium-rich solution after concentration in Comparative Example 3 is not deeply purified, and the solution contains significantly excessive calcium and magnesium ions. When the concentration of lithium ions reaches 18g / L, the calcium ion concentration in the concentrated lithium solution is 10mg / L and the magnesium ion concentration is 15mg / L. In Example 3, the ion exchange resin method is used to deeply adsorb metal ions such as calcium, magnesium, aluminum, and iron in the solution, and a special special resin material CH-93 resin is used. After deep impurity removal, the solution contains 0.2mg / L of calcium and 0.08mg / L of magnesium ions. The heavy metal ions such as aluminum, iron, and manganese are all less than 0.1mg / L, and the solution meets the requirements for preparing battery-grade lithium carbonate.

[0182] Therefore, the lithium-rich solution must be deeply purified and impurities removed, and this step cannot be omitted.

[0183] Comparative Example 4

[0184] Referring to the method in Example 1, battery-grade lithium carbonate is prepared using clay-type lithium ore. The other steps are the same as those in Example 1, except that: in step (6) of preparing battery-grade lithium carbonate in Example 4, the order of adding materials is different from that in Example 1. In Example 4, saturated sodium carbonate solution is added to the lithium-rich solution.

[0185] Comparative Example 4 adopts the sequential addition method (i.e., adding the saturated sodium carbonate solution to the lithium-rich solution), and the one-time lithium precipitation recovery rate is lower than that of the reverse addition method adopted in Example 1 (i.e., adding the lithium-rich solution to the saturated sodium carbonate solution), and the dispersion effect and crystal state of the product are significantly worse than those of the reverse addition method adopted.

[0186] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0187] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A method for preparing battery-grade lithium carbonate from clay-type lithium ore, characterized in that: include: The clay-type lithium ore is roasted, leached and iron-removed to obtain an iron-removed solution; The iron-removed solution is mixed with an inorganic base to react to obtain a lithium-containing aluminum hydroxide precipitate adsorbent; Separating the lithium from the aluminum hydroxide precipitate adsorbed lithium to obtain aluminum oxide powder and a lithium-containing solution; The lithium-containing solution is subjected to a decalcification and magnesium treatment and a concentration treatment to obtain a lithium-rich solution; Deeply purifying and removing impurities from the lithium-rich solution to obtain a purified lithium-rich solution; reacting the purified lithium-rich solution with sodium carbonate to obtain battery-grade lithium carbonate; The lithium-aluminum separation of the lithium-containing aluminum hydroxide precipitate adsorbent comprises: calcining the lithium-containing aluminum hydroxide precipitate adsorbent to obtain a calcined product; mixing the calcined product with water and an additive to leach lithium attached to the calcined product, filtering, and obtaining aluminum oxide and a lithium-containing solution; Wherein, the additive includes at least one of NaCl, NH4Cl, CaCl2, and MgCl2; The content of the additive in the solution formed by the water and the additive is 1-6wt%; The lithium-containing solution is subjected to a calcium-magnesium removal treatment and concentrated into a lithium-rich solution, comprising: The lithium-containing solution is mixed with a decalcification and magnesium reagent to carry out a decalcification and magnesium reaction to obtain a calcium and magnesium slag and a solution after decalcification and magnesium removal; The solution after calcium and magnesium removal is evaporated and concentrated to obtain a lithium-rich solution; The decalcification and magnesium reagent includes at least one of sodium carbonate and EDTA; The concentration of the decalcification and magnesium reagent in the reaction system is 5-10wt%; The pH of the decalcification and magnesium reaction is 9.0-10; The temperature of the decalcification and magnesium reaction is 20°C to 25°C; The concentrations of calcium and magnesium ions in the solution after calcium and magnesium removal are both less than 0.02 g / L; The concentration of calcium ions in the lithium-rich solution is less than 50 mg / L, and the concentration of magnesium ions in the lithium-rich solution is less than 16 mg / L; The step of reacting the purified lithium-rich solution with sodium carbonate comprises: adding the purified lithium-rich solution to a saturated sodium carbonate solution for reaction.

2. The method for preparing battery-grade lithium carbonate from clay-type lithium ore according to claim 1, characterized in that: The pH of the reaction system after the iron removal solution is mixed with the inorganic base is 5.0-7.0; And / or, the temperature of the reaction between the deironing solution and the inorganic base is 40° C. to 70° C.; And / or, the inorganic base comprises NaOH.

3. The method for preparing battery-grade lithium carbonate from clay-type lithium ore according to claim 1, characterized in that: The calcination temperature is 350°C to 500°C; And / or, the pH of the solution during the mixed leaching is 5 to 9; And / or, the temperature of the mixed leaching is 40°C to 70°C.

4. The method for preparing battery-grade lithium carbonate from clay-type lithium ore according to claim 1, characterized in that: Deeply purifying and removing impurities from the lithium-rich solution includes: mixing the lithium-rich solution with an ion exchange resin, removing impurity ions through the action of the ion exchange resin, and obtaining a purified lithium-rich solution through a separation step.

5. The method for preparing battery-grade lithium carbonate from clay-type lithium ore according to claim 1, characterized in that: The temperature at which the purified lithium-rich solution reacts with sodium carbonate is 85-95° C.; And / or, the excess coefficient of sodium carbonate is 1.1 to 1.2; And / or, the feeding time of the purified lithium-rich solution is 30 to 40 minutes, the reaction time of the purified lithium-rich solution and sodium carbonate is 60 to 70 minutes, and the method further includes standing after the reaction is completed, and then filtering; the standing time is 30 to 40 minutes.

6. The method for preparing battery-grade lithium carbonate from clay-type lithium ore according to claim 5, characterized in that: After the purified lithium-rich solution reacts with sodium carbonate, the method further comprises: filtering the ore pulp after the reaction to obtain lithium carbonate precipitate and lithium precipitation liquid; washing the lithium carbonate precipitate with water for multiple times to obtain battery-grade lithium carbonate.

7. The method for preparing battery-grade lithium carbonate from clay-type lithium ore according to claim 6, characterized in that: The washing is performed at least twice, and the washing temperature is 85-95°C.

8. The method for preparing battery-grade lithium carbonate from clay-type lithium ore according to any one of claims 1 to 7, characterized in that: The process of roasting, leaching and removing iron from the clay-type lithium ore comprises: Roasting the clay-type lithium ore to obtain roasted sand; The roasted sand is mixed with an inorganic acid and leached to obtain a leachate; The leaching solution is mixed with the roasted sand and calcium oxide, iron is removed, and then filtered to obtain iron slag and a solution after iron removal.

Citation Information

Patent Citations

  • Method for preparing lithium chloride and method for preparing lithium carbonate

    CN109689573A

  • Method for extracting lithium from low-aluminum lithium-rich clay

    CN114934196A

  • Method for preparing lithium carbonate from lithium-containing waste residues and application thereof

    CN116835614A

  • Clay lithium ore raw ore calcine leaching process and method for removing iron from leachate of clay lithium ore raw ore calcine

    CN118147456A

Cited By

  • Comprehensive utilization method of clay type lithium ore

    CN121700199A

  • A comprehensive utilization method for clay-type lithium deposits

    CN121700199B